Lymnastis of Ukraine with the redescription of Lymnastis novikovi (Coleoptera: Carabidae) - Kirichenko, Marina B.; Gontarenko, Andrej V. (Zootaxa, 2013)
The rare species Lymnastis novikovi Michailov, 1998, described from the single female specimen collected in Ukraine, is redescribed on the basis of new material. We provide the illustrations of the general habitus, the median lobe and its in-ternal sac and describe the habitat of L. novikovi, to increase information about this species. A key to European Lymnastis species is given. The current distribution of Lymnastis galilaeus Piochard de la Brûlerie, 1876 and L. novikovi in Ukraine is described.